2006
DOI: 10.1002/gps.1671
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic accuracy of the Cognitive Performance Scale (Minimum Data Set) and the Mini‐Mental State Exam for the detection of cognitive impairment in nursing home residents

Abstract: SUMMARYObjectives To examine the evolution of quality of life (QOL) in demented subjects at base-line, one and 2 years later and to determine clinical variables associated with QOL. Method Longitudinal study of a cohort of 127 subjects living at home or in a long-term care institution. A QOL measure (Alzheimer Disease Related Quality of Life; ADRQL) was administered three times. In addition, several clinical instruments (MMSE, IADL, ADL and CDR/M) were also administered. Results ADRQL data analysis did not rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 24 publications
0
69
0
Order By: Relevance
“…The CPS has been shown to have a significant positive correlation with the Mini-Mental State Examination (MMSE) and is scored on a 0-6 scale, with 0 corresponding to No Impairment (intact) and 6 corresponding to Very Severe Impairment. [9][10][11] Nursing home patients with significant cognitive impairment may have difficulty utilizing handheld device (HHD) formulations (metered-dose or dry powder inhalers) of COPD medications and may be clinically appropriate candidates for nebulized therapy. 12 The objective of this study was to develop a "profile" of patients in nursing homes with a diagnosis of COPD, including but not limited to pertinent demographic information, concurrent diagnoses, medications used in the treatment of COPD, other concomitant medications, and numerous functional (e.g., ability to ambulate independently) and quality of life (e.g., oxygen use) parameters extracted from the MDS and pharmacy claims data.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
“…The CPS has been shown to have a significant positive correlation with the Mini-Mental State Examination (MMSE) and is scored on a 0-6 scale, with 0 corresponding to No Impairment (intact) and 6 corresponding to Very Severe Impairment. [9][10][11] Nursing home patients with significant cognitive impairment may have difficulty utilizing handheld device (HHD) formulations (metered-dose or dry powder inhalers) of COPD medications and may be clinically appropriate candidates for nebulized therapy. 12 The objective of this study was to develop a "profile" of patients in nursing homes with a diagnosis of COPD, including but not limited to pertinent demographic information, concurrent diagnoses, medications used in the treatment of COPD, other concomitant medications, and numerous functional (e.g., ability to ambulate independently) and quality of life (e.g., oxygen use) parameters extracted from the MDS and pharmacy claims data.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
“…For the purposes of this analysis, moderate-to-severe cognitive impairment was defined as CPS scores of 3-6. 10 The CDI incidence rate per 10,000 resident days was calculated as the number of CDI incidents per month per number of resident days × 10,000. The calculation excludes recurrent events.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
“…The Cognitive Performance Scale (CPS) (Morris, et al, 1994) was developed from five MDS items and is reported both reliable and valid when an individual is trained on its use (Paquay, et al, 2007). Wu and colleagues (2003) quantified the severity of cognitive impairment with the CPS into three categories, no or mild CI (0-1), moderate CI (2-3), and severe CI (4-6).…”
Section: Measuring Cognitive Impairmentmentioning
confidence: 99%
“…The CPS is a reliable and valid measure of cognitive decline that also uses specific MDS items (Paquay, et al, 2007). The CPS is scored from 1 (borderline intact) to 6 (very severe impairment).…”
Section: Assessing Pain In Nursing Home Residents With Cognitive Impamentioning
confidence: 99%
See 1 more Smart Citation